Design and fabrication of a solar-dish concentrator with 2-axis solar tracking system - Pongnarin Savangvong; Banterng Silpsakoolsook; Sutapat Kwankoameng (My University, 2021)
Abstract This paper presents an economical parabolic solar collector including design analysis, fabrication, and testing of the solar concentrator with a dual-axis solar tracking system. The design goals of the solar dish are high concentrating temperature and power density but low weight and cost. To achieve a high-efficiency dish, minimizing loss is important therefore the design focuses on high reflectability, low heat absorption with an optimum dish profile. The dish is a parabolic shape with two layers of different materials. Three reflector materials, an emergency blanket, PET-Mirror, and Mirror are introduced on the top layer as the solar reflectance. The second layer, fiberglass that is lightweight, easy to shape up in various features, and cheap, is used as a dish structure. The dish is installed with a 2-axis solar tracking system and supported by a steel column. The ¼ inch copper tube is coiled as a receiver. The receiver is placed at the focal point of the solar dish. To evaluate the heat at the focal point, water is pumped through the receiver coil to absorb the heat from the focal point. The heat output of the solar dish is calculated from the temperature difference of the water inlet and outlet of the receiver coil. The temperature at the focal point was presented along with the heat power output, and solar dish efficiency.
Keywords: Parabolic reflector; Reflector (photography); Concentrator; Focal point; Heliostat; Solar Thermal and Photovoltaic Systems